First Resort: Alternative Dispute Resolution for Breach of Verbal Purchase Agreements: Penyelesaian Sengketa Alternatif: Pilihan Utama untuk Menyelesaikan Pelanggaran Kesepakatan Pembelian Verbal dalam Bisnis - Anggun Sukma; Sri Budi Purwaningsih (Universitas Muhammadiyah Sidoarjo, 2023)
Disputes over breach of verbal purchase agreements often occur in society, particularly in the business sector. The purpose of this study is to analyze efforts to resolve such disputes based on Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution. The research method used is normative research. The results of this study show that efforts to resolve disputes over breach of verbal purchase agreements can be carried out through non-litigation based on the selection of Alternative Dispute Resolution methods, such as Negotiation, Mediation, Conciliation, and Arbitration based on Law No. 30/1999. Non-litigation resolution is intended as the first resort and considers the court as a last resort, in addition, the evidence tools as regulated in Article 1866 of the Civil Code need to be presented because the agreement was made verbally. Highlights : Disputes over breach of verbal purchase agreements are common in the business sector. Alternative Dispute Resolution methods such as negotiation, mediation, conciliation, and arbitration can be used to resolve disputes based on Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution. Non-litigation resolution is the preferred approach, with the court being considered as a last resort, and evidence tools as regulated in Article 1866 of the Civil Code need to be presented for verbal agreements. Keywords: Alternative Dispute Resolution, Verbal Purchase Agreements, Non-litigation, Law No. 30/1999, Evidence Tools